2015
DOI: 10.1016/j.apjtb.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of extra pulmonary tuberculosis in Eastern Sudan

Abstract: A B S T R A C TObjective: To investigate the epidemiological factors associated with extra pulmonary tuberculosis (EPTB) in Kassala, Eastern Sudan. Methods: Patients infected with TB (pulmonary and extra-pulmonary) documented at the hospital were interviewed with a structured questionnaire used to gather sociodemographic information. The diagnosis of EPTB cases was based on presence of tuberculous granulomas in the histological samples, positive PCR to DNA of mycobacterium tuberculosis, radiological findings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
(24 reference statements)
3
8
0
Order By: Relevance
“…Our results also demonstrated that smoking was not associated with EPTB which is consistent with other studies [ 21 ] and smoking was reported as the risk factor for PTB compared with EPTB [ 32 ]. Similarly, in our study occupation and residence of participants were not associated with EPTB which is in agreement with study conducted in Sudan [ 21 ]. In the present study, only two samples demonstrated rifampicin resistant Mycobacterium tuberculosis complex making the prevalence of rifampicin resistant-TB 6.5% (2/31).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results also demonstrated that smoking was not associated with EPTB which is consistent with other studies [ 21 ] and smoking was reported as the risk factor for PTB compared with EPTB [ 32 ]. Similarly, in our study occupation and residence of participants were not associated with EPTB which is in agreement with study conducted in Sudan [ 21 ]. In the present study, only two samples demonstrated rifampicin resistant Mycobacterium tuberculosis complex making the prevalence of rifampicin resistant-TB 6.5% (2/31).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, studies conducted in other countries showed TB lymphadenitis as the common form of EPTB followed by pleural forms [ 18 20 ]. Recent reports from Sudan also indicated that TB lymphadenitis is the most frequent form of EPTB followed by peritoneal TB [ 21 ]. In contrast, other reports have shown pleural effusion as the most frequent form of EPTB, followed by lymphatic TB [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The country accounts for 15% of the TB burden in the WHO Region for the Eastern Mediterranean (8). It was recently observed that 26.6% of patients with TB in the Region had extra-pulmonary TB (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…An extensive review on the causes of pericarditis conducted by Noubiap JJ, et al revealed that M. tuberculosisis a responsible agent in pericarditis, but not hemorrhagic pericarditis, and furthermore, no unique 2D-echocardiographic signs were detected [9]. A cross-sectional study from Sudan between January 2011 and June 2012 enrolled 985 patients, 22.7% (224) were extrapulmonary tuberculosis, only 1.9% [4] patients were pericardial, and none were hemorrhagic [10]. Our patient diagnosis was firmly based on bacterial culture (Figure 4), and on pericardial biopsywith the characteristic picture (Figure 2 A, B) and AFB on Ziehl-Neelsen stain of the pericardial biopsy (Figure 3).…”
Section: Discussionmentioning
confidence: 99%